Household structure is independently associated with malaria risk in rural Sussundenga, Mozambique - Searle, Kelly M.; Earland, Dominique; Francisco, Albino; Muhiro, Valy; Novela, Anisío; Ferrão, João (Frontiers in Epidemiology, 2023)
Background: Mozambique has the 4 th highest malaria cases and malaria mortality globally. Locally, malaria incidence increases from low in the southern region to high in the central and northern regions. Manica Province in central Mozambique has the 4 th highest prevalence of malaria out of the 11 provinces, and the highest in the central region of the country. In this area where coverage of interventions has been limited, household level risk factors can be important for understanding the natural history of infection, as well as the implementation of current and future interventions. There has been indication that the relationship between household structure and malaria risk is actually a mediating one between the true relationship between household income and education and P. falciparum infection. The objective of this study was to determine and quantify these complex relationships. Methods: We conducted a community-based cross-sectional study in Sussundenga village. Sussundenga is a rural village, located in Sussundenga District, Manica Province, Mozambique. We enrolled 303 participants from 83 randomly selected households. We collected information on demographics, household construction, and administered a P. falciparum rapid diagnostic test. We constructed several generalized estimating equations logistic regression models to determine the independent effects of housing construction on malaria risk. We also constructed models separate generalized estimating equations logistic mediation models to determine the proportion of effects mediated by household construction material in the relationship between head of household occupation and education and malaria risk. Results: The overall malaria prevalence among the study population by RDT was 30.8%. In the multivariable model adjusting for all individual and household factors as potential confounders, rudimentary roof structure was the only household structural variable that was statistically significantly associated with increased malaria risk ). We found no evidence that household structure mediated the relationship between head of household education or employment and malaria risk in our study population. Conclusion: Household structure was a significant risk factor for malaria infection in our study population. These findings are consistent with malaria being a disease of poverty and an area that could be targeted for future interventions that could have longterm impacts.